2011
DOI: 10.1063/1.3621858
|View full text |Cite
|
Sign up to set email alerts
|

On the validity of the Navier-Stokes equations for nanoscale liquid flows: The role of channel size

Abstract: In this work, we investigate the validity of the Navier-Stokes (NS) equations for nanoscale liquid flows through molecular dynamics simulations. We focus on the role of channel size by considering the fluid-wall interaction. Liquid flows between two planar parallel walls driven by an external force with channel size ranging from 2 to 80 nm are studied. The volumetric flux is computed and the dependence of the volumetric flux on the channel size is explained both qualitatively and quantitatively. It is found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 38 publications
3
50
0
Order By: Relevance
“…Therefore, the geometrical boundaries of each sub-domain cannot be determined in advance, as they result from molecular dynamics. Taking into consideration that we need to discretize the equations to perform simulations and numerical experiments, and that we are dealing at the very validity limit of continuous flow models [29], our chance of getting close to helpful and interesting solutions in this way is not very likely.…”
Section: Principal Thoughts About Strategic Choicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the geometrical boundaries of each sub-domain cannot be determined in advance, as they result from molecular dynamics. Taking into consideration that we need to discretize the equations to perform simulations and numerical experiments, and that we are dealing at the very validity limit of continuous flow models [29], our chance of getting close to helpful and interesting solutions in this way is not very likely.…”
Section: Principal Thoughts About Strategic Choicesmentioning
confidence: 99%
“…Therewith, we analyze cellular compensatory mechanisms for replacing the molecules consumed by polymerization, subject to the principle of mass conservation. Cytosol has a colloidal-water constitution which, in first approximation, leads to considering it as an incompressible and viscous fluid and modeling its motion by Navier-Stokes equations for incompressible fluid flow [29],…”
Section: Modeling Cytosolic Flow As a Means To Drive Passive Transpormentioning
confidence: 99%
“…Liu and Li showed that when the channel height was sufficiently large, the Navier-Stokes equation was still valid; While for a very small channel height, the Navier-Stokes equation failed (Liu and Li, 2011). Roohi and Darbandi (2009) modified the Navier-Stokes equation for solving the velocity distribution in micro/nano channel flows by using the slip boundary conditions and the viscosity coefficient (i.e.…”
Section: The Modified Navier-stokes Equation Modelmentioning
confidence: 99%
“…By using the Lennard-Jones potential model in MDS, Liu and Li (2011) showed that the Navier-Stokes equation can be valid for the channel height greater than 50nm, regardless of the fluid-wall interaction; For a nano channel height on the 1nm scale, MDS should normally be used to simulate the fluid flow inside the channel to capture the special flow characteristic; The flow was heavily dependent on the fluid-wall interaction.…”
Section: Full Mds Modelmentioning
confidence: 99%
See 1 more Smart Citation